Sharia Governance Climate, Psychological Safety, and AuditorDiscretionary Disclosure Behavior - Novi Yanti; Syamsurizal; Gehad Mohammed Sultan Saif (Journal Economic Business Innovation, 2026)
Purpose — This study examines how oversight leadership openness, management dominance pressure, governance transparency climate, and auditor moral courage influence auditor discretionary disclosure behavior within Sharia-governed financial institutions. Design/methodology/approach — Drawing on psychological safety theory, accountability and authority perspectives, and ethical leadership theory integrated with Islamic governance principles, this research employs a quantitative approach using survey data from governance and audit professionals in two emerging Islamic financial contexts. Findings — The findings indicate that leadership openness, transparency climate, and moral courage positively enhance discretionary disclosure, whereas management dominance pressure suppresses it. Crucially, psychological safety emerges as a central explanatory mechanism that translates governance conditions into disclosure behavior. The moderating role of Sharia governance ethical climate appears limited, suggesting that ethical norms function more as foundational governance values rather than as interactional amplifiers in this specific behavioral context. Originality/value — This study contributes to governance and auditing literature by integrating relational safety mechanisms with Sharia-based oversight principles. It offers a novel perspective by identifying psychological safety as the primary conduit through which governance structures and individual ethical capacities shape disclosure behavior, moving beyond purely structural or compliance-based views of Sharia auditing. Implications — The results offer practical implications for strengthening transparency, accountability, and ethical reporting in Islamic financial institutions. They suggest that to improve disclosure, organizations must prioritize cultivating a psychologically safe environment and reducing management dominance, rather than relying solely on formal ethical codes or structural compliance.